2023
DOI: 10.1136/bmjopen-2023-073652
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of integrated chronic care models for cardiometabolic multimorbidity in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: ObjectivesThis review aimed at identifying the elements of integrated care models for cardiometabolic multimorbidity in sub-Saharan Africa (SSA) and their effects on clinical or mental health outcomes including systolic blood pressure (SBP), blood sugar, depression scores and other patient-reported outcomes such as quality of life and medication adherence.DesignSystematic review and meta-analysis using the Grading of Recommendation, Assessment, Development and Evaluation (GRADE) approach.Data sourcesWe systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“… 27 In sub-Saharan Africa, there was moderate-grade evidence for integrated care models in primary care settings for people with cardiometabolic morbidity. 28 A Cochrane review of the interventions for multimorbidity published in 2021 could not make strong recommendations for the care of people with multimorbidity but suggested that organisational changes that target specific problems and align with outcomes of interest specific to the patient could be successful and that more research was needed. This review included 17 RCTs, all from HICs.…”
Section: Introductionmentioning
confidence: 99%
“… 27 In sub-Saharan Africa, there was moderate-grade evidence for integrated care models in primary care settings for people with cardiometabolic morbidity. 28 A Cochrane review of the interventions for multimorbidity published in 2021 could not make strong recommendations for the care of people with multimorbidity but suggested that organisational changes that target specific problems and align with outcomes of interest specific to the patient could be successful and that more research was needed. This review included 17 RCTs, all from HICs.…”
Section: Introductionmentioning
confidence: 99%